Merger and acquisition : impact on shareholder returns / Madiha A. Majid - A. Majid, Madiha (Faculty of Business Management, 1995)
Merger and takeover are popular strategy in order to expand or verified production or activities in the company. However, the study on the impact of takeover and merger in shareholder retains on the target and acquired companies are so little done by the local security industry. This study observed daily share market returns with regard to the first announcement of merger and takeover activity, 50 days prior to and 50 days after the announcement of the merger said takeover proposal.